The Effect of Ductoscopy in the Surgical Selection of Patients with Pathological Nipple Discharge - Kenan Çetin (Southern Clinics of Istanbul Eurasia, 2019)
INTRODUCTION[|]Surgical excision of the ductus is the current conventional means of treatment and diagnosis of pathological nipple discharge (PND). However, a review of the histopathology results of cases of routine duct excision reveals that a large number of unnecessary surgical interventions are performed. The aim of this study was to determine the rate of lesion detection after a ductoscopic evaluation in patients who underwent surgery. [¤]METHODS[|]November 2005 and December 2010, a microductectomy was performed following a ductoscopic evaluation for 129 patients who were admitted to our clinic with PND. The characteristics of the discharge, and the ductoscopic and pathological findings were assessed. [¤]RESULTS[|]The final pathology results confirmed lesions in 76% of the patients (85/112) who underwent surgery based on only ductoscopic findings. Seventeen patients with ductoscopic findings who were operated on based on the findings of a physical examination and classical imaging methods could be followed up. Lesions were detected in 11 (6 potential neoplastic and malignant lesions, 5 papillomatous lesions). [¤]DISCUSSION AND CONCLUSION[|]The results of this study indicate that ductoscopy appears to predict the patients who will require surgical treatment and so can decrease the number of operations. However, conventional imaging and physical examination findings of patients should also be considered in the follow-up after ductoscopy in PND patients.[¤]